Una muchedumbre o nada Coordenadas temáticas en la obra poética de Josefina Plá - DI MEGLIO, FRANCESCA (Biblioteca di Studi di Filologia Moderna, 2018)
Una muchedumbre o nada. Coordenadas temáticas en la obra poética de Josefina Plá investigates the aspects still little studied and offers new interpretations of the poet's work (Canary Islands 1903 - Asunción 1999). The intertextual analysis, which has explored not only the verses but also the stories, essays and plays, has revealed a network of relationships, metaphors and thematic axes (such as erotic passion, the yearning for motherhood or the meditations on the multiplicity of the individual and the relationship with time and death) that develops both internally, between the various fields of the author's production, and externally, establishing explicit links or revealing implicit affinities with authors such as Rokha, Unamuno, Pirandello, Seneca, Heidegger or García Lorca.